VD_FINDINFO HC / 2025 / 878 vom 19. November 2025 - VD Tribunal cantonal (2025)
ACTION EN DIVORCE, CAUSE DE DIVORCE, COMPÉTENCE RATIONE LOCI | 25 LDIP, 65 LDIP, 9 al. 1 LDIP, 9 al. 2 LDIP, 9 al. 3 LDIP, 9 LDIP